The nature of the conflict in Ezra-Nehemiah 1 - Wyk, Wouter C. van (HTS teologiese studies, 2001)
The text of Ezra-Nehemiah relects a severe conlict situaion in post-exilic Judaean society. However, the text is unclear about crucial issues such as the identity of the parties involved, the aims of the different parties, and even the roots of the conlict. A close analysis of the text reveals that what is portrayed as an external conlict clearly has a serious internal dimension too. The heart of the conlict lies not so much in disputes over land and building rights, but rather in the central issue of access to the community of returned exiles.